2012
DOI: 10.1155/2012/657942
|View full text |Cite
|
Sign up to set email alerts
|

EhADH112 Is a Bro1 Domain-Containing Protein Involved in theEntamoeba histolyticaMultivesicular Bodies Pathway

Abstract: EhADH112 is an Entamoeba histolytica Bro1 domain-containing protein, structurally related to mammalian ALIX and yeast BRO1, both involved in the Endosomal Sorting Complexes Required for Transport (ESCRT)-mediated multivesicular bodies (MVB) biogenesis. Here, we investigated an alternative role for EhADH112 in the MVB protein trafficking pathway by overexpressing 166 amino acids of its N-terminal Bro1 domain in trophozoites. Trophozoites displayed diminished phagocytosis rates and accumulated exogenous Bro1 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 47 publications
0
58
0
1
Order By: Relevance
“…The presence of EhADH (one of the two proteins forming the EhCPADH complex) in MVB‐like structures was previously evidenced (Banuelos et al, ; Castellanos‐Castro et al, ). In addition, Castellanos‐Castro et al () showed the co‐localisation of EhADH with lysobisphosphatidic acid, a phospoholipid that in eukaryotes is only detected in late endosomes.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The presence of EhADH (one of the two proteins forming the EhCPADH complex) in MVB‐like structures was previously evidenced (Banuelos et al, ; Castellanos‐Castro et al, ). In addition, Castellanos‐Castro et al () showed the co‐localisation of EhADH with lysobisphosphatidic acid, a phospoholipid that in eukaryotes is only detected in late endosomes.…”
Section: Discussionmentioning
confidence: 81%
“…Trophozoites were incubated for 0, 2, 10, 15, 20, 30, and 60 min with RBCs (1:25) at t 37°C for phagocytosis experiments (Banuelos et al, ; Garcia‐Rivera, Sanchez, Orozco, & Guarneros, ) at 37°C for phagocytosis assays or 4°C for adhesion assays for 0, 2, 10, 15, 20, 30, and 60 min. Preparations were quickly washed three times with PBS 1X or TYI‐water (1:1) and prepared for immunofluorescence (Banuelos et al, ; Bolanos et al, ), immunoelectron microscopy, western blot assays, and immunoprecipitation.…”
Section: Methodsmentioning
confidence: 99%
“…histolytica trophozoites lack typical cellular structures present in higher eukaryotes, such as mitochondria, Golgi apparatus and a well-differentiated endoplasmic reticulum (Ghosh et al, 1999). The parasite uses primitive organelles that through a dynamic and complex vesicle trafficking perform their corresponding functions (Bañuelos et al, 2012), which remarks the importance of lipids in virulence. In addition, lipids also work as signaling molecules, energy stores, post-translational modifiers and inclusive, as virulence factors (Shrimal et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpressed ADH112 localizes to the plasma membrane and cytoplasmic vesicles and accumulates on MVBs, and can interact with the ESCRT subunit Vps32. Expression of exogenous Bro1 has a dominant negative effect on red blood cell phagocytosis [101], suggesting a possible role for ESCRT machinery in this process.…”
Section: Functional Homology In Trafficking Machinery Between Divermentioning
confidence: 99%